Incidencia de las estrategias de enseñanza aprendizaje en los aprendices del programa Electricidad Industrial del Centro Industrial de Mantenimiento Integral - García Serrano, Saúl Ernesto
The purpose of the research is to determine the impact on the training of apprentices of the Industrial Electricity program in the Integral Maintenance Industrial Center, the E-A strategies in their training process to acquire competences. The studies on the strategies have a literature of theoretical and practical referents very broadly standing out in the case of the Sena, the contribution of Parra Pineda (2003) of the Antioquia Regional where it points out the strategies centered on the student, the teacher,the object of knowledge, and the process and / or didactic mediations; However, studies on the effects on the execution of the training process are known in the institution. It is intended then to make a contribution to the impact offered in the classroom didactic strategies E-A taking a population of 100 apprentices and 10 teachers of epistemic knowledge of the Electricity Network, using a qualitative descriptive analytical methodology